CRAFTS FARRASH DURING THE MAMLUK ERA(648-923H/1250-1517AD) SOCIOECONOMIC STUDY - Ahmed, Dilman Ahmed (Humanities Journal of University of Zakho, 2026)
Islamic society witnessed a wide diversity of professions and crafts, where each profession was distinguished by its own social and economic characteristics and roles. Its status also varied depending on the nature of its function and importance. Within the scope of studying the social and economic history of the Mamluk state, this study tackles the profession of "Farrash" (sweeper) as one of the professions that enjoyed a privileged status, even its practitioners received support and patronage from the ruling authorities.The study focuses on analyzing the meaning of the term "Farrash" in the Mamluk context, exploring the social and economic aspects of the lives of practitioners of this profession. It also examines the interactions of Mamluk sultans and princes with them, and traces the most prominent figures in this profession. The study also addresses the issue of precisely defining the ranks and functional duties of this profession, observing its position in the social structure, and the general outlook on it in Mamluk society.The research problem concentrates on answering the following questions: What is the linguistic and terminological meaning of the term (Farrash)? How did the Mamluk sultans and princes deal with the people of this profession? What was the nature of the social and economic life of its practitioners? Who were the most prominent figures who practiced this profession in the Mamluk era? How was the organization of the ranks of this profession and selecting its function precisely? What was the Mamluk society's view of this profession? What were the most prominent places found in this profession?